An Investigative Look at Healthcare Beliefs and Practices During the Sen Dynasty - Beine, Dave (Dhaulagiri Journal of Sociology and Anthropology, 2013)
There is not much known about Nepal during the historical period sometimes referred to as Nepal’s dark ages (750-1750 C.E.). And even less is known about the healthcare practices of the Sen Dynasty of Palpa, Nepal, which found its inception over 500 years ago, during the late fifteenth century. For this reason, anyone endeavoring to intelligently write on the subject must, much like an archaeologist, use a bit of educated conjecture to piece together a speculative, but historically plausible, picture of the healing practices likely employed during that period. In order to do so, this paper examines several pieces of evidence, both historic and contemporary, in order to infer what the healthcare practices of the populace of Palpa might have looked like at that time. DOI: http://dx.doi.org/10.3126/dsaj.v6i0.8479 Dhaulagiri Journal of Sociology and Anthropology Vol. 6, 2012 61-74